Non-compaction cardiomyopathy – brief review - Oana Mirea; Mihaela Berceanu; Anca Constantin; Mirela Mănescu; Georgică C. Târtea; Ionuț Donoiu; Constantin Militaru; Octavian Istrătoaie (Journal of Mind and Medical Sciences)
Left ventricular non-compaction cardiomyopathy is a genetic disorder characterized by the presence of two myocardial layers with numerous prominent trabeculations and deep inter-trabecular recesses that communicate with the ventricular cavity. The diagnosis is often challenging because excessive trabeculations may also be a normal finding in performance athletes and black people. Echocardiography is the gold standard for diagnosis of this condition, but other useful diagnostic techniques may include cardiac magnetic resonance imaging, computed tomography, and contrast ventriculography. Moreover, newer echocardiographic methods such as three-dimensional imaging and speckle tracking analysis promise to improve the diagnosis of left ventricular non-compaction cardiomyopathy. The purpose of this paper is to review the pathogenesis, diagnosis, and management of this disease.